Use of psychotropic drugs following venous thromboembolism in youth. A nationwide cohort study. Issue 4 (April 2015) - Højen, Anette Arbjerg; Gorst-Rasmussen, Anders; Lip, Gregory Y.H.; Lane, Deirdre A.; Rasmussen, Lars Hvilsted; Sørensen, Erik Elgaard; Larsen, Torben Bjerregaard
Abstract: Introduction: The mental health prognosis following a venous thromboembolism in youth has not been investigated comprehensively. Using psychotropic drug purchase as a proxy for mental health status, we investigated this issue in a large cohort of young incident venous thromboembolism patients. Methods: Using Danish nationwide administrative registries from the period 1997–2010, we identified 4, 132 patients aged 13–33 years with a first-time venous thromboembolism diagnosis and no history of psychotropic drug usage. We sampled comparison cohort of random general population controls, matched individually in a 1:5 ratio based on sex and birth year. Participants were followed in prescription purchase registries for their first psychotropic drug purchase. Results: Among young venous thromboembolism case cases, the 1-year risk of psychotropic drug purchase was 7.1% (95% confidence interval [CI] 6.3, 7.9) and the 5-year risk 22.1% (95% CI 20.7, 23.5). This was substantially higher than among population controls, with 1- and 5-year risk differences relative to the controls of 4.7% (95% CI 3.9, 5.5), and 10.8% (95% CI 9.4, 12.3), respectively. Adjustment for the effects of recent pregnancy or somatic provocations attenuated risk differences to 4.1% (95% CI 3.5, 5.1) after 1 year and 9.6% (95% CI 8.3, 11.2) after 5 years. Conclusions: A venous thromboembolism diagnosis in youth is associated with a poorer mental health prognosis: one in five patients are prescribed psychotropic medication within the first 5 year after diagnosis. Highlights: VTE in the young is associated with a poor mental health prognosis 1 in 5 patients purchase psychotropic drugs within 5 years after VTE diagnosis Among similarly aged peers, only 1 in 10 purchase psychotropics in the same period Young VTE patients may need long-term followup with a focus on mental health